MAYBE Initial complexity problem: 1: T: (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] (1, 1) f3(a, b, c) -> f2(a, b, c) (?, 1) f2(a, b, c) -> f300(a + b, b, d) [ 0 >= a + b + 1 ] start location: f3 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] (1, 1) f3(a, b, c) -> f2(a, b, c) start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b, c) with all transitions in problem 2, the following new transition is obtained: f3(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] We thus obtain the following problem: 3: T: (1, 2) f3(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] with all transitions in problem 3, the following new transition is obtained: f3(a, b, c) -> f2(a + 2*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 ] We thus obtain the following problem: 4: T: (1, 3) f3(a, b, c) -> f2(a + 2*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 2*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 ] with all transitions in problem 4, the following new transition is obtained: f3(a, b, c) -> f2(a + 3*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 ] We thus obtain the following problem: 5: T: (1, 4) f3(a, b, c) -> f2(a + 3*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 3*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 ] with all transitions in problem 5, the following new transition is obtained: f3(a, b, c) -> f2(a + 4*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 ] We thus obtain the following problem: 6: T: (1, 5) f3(a, b, c) -> f2(a + 4*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 4*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 ] with all transitions in problem 6, the following new transition is obtained: f3(a, b, c) -> f2(a + 5*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 ] We thus obtain the following problem: 7: T: (1, 6) f3(a, b, c) -> f2(a + 5*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 5*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 ] with all transitions in problem 7, the following new transition is obtained: f3(a, b, c) -> f2(a + 6*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 ] We thus obtain the following problem: 8: T: (1, 7) f3(a, b, c) -> f2(a + 6*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 6*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 ] with all transitions in problem 8, the following new transition is obtained: f3(a, b, c) -> f2(a + 7*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 ] We thus obtain the following problem: 9: T: (1, 8) f3(a, b, c) -> f2(a + 7*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 7*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 ] with all transitions in problem 9, the following new transition is obtained: f3(a, b, c) -> f2(a + 8*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 ] We thus obtain the following problem: 10: T: (1, 9) f3(a, b, c) -> f2(a + 8*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 8*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 ] with all transitions in problem 10, the following new transition is obtained: f3(a, b, c) -> f2(a + 9*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 ] We thus obtain the following problem: 11: T: (1, 10) f3(a, b, c) -> f2(a + 9*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 9*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 ] with all transitions in problem 11, the following new transition is obtained: f3(a, b, c) -> f2(a + 10*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 ] We thus obtain the following problem: 12: T: (1, 11) f3(a, b, c) -> f2(a + 10*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 10*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 ] with all transitions in problem 12, the following new transition is obtained: f3(a, b, c) -> f2(a + 11*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 ] We thus obtain the following problem: 13: T: (1, 12) f3(a, b, c) -> f2(a + 11*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 11*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 ] with all transitions in problem 13, the following new transition is obtained: f3(a, b, c) -> f2(a + 12*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 ] We thus obtain the following problem: 14: T: (1, 13) f3(a, b, c) -> f2(a + 12*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 12*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 ] with all transitions in problem 14, the following new transition is obtained: f3(a, b, c) -> f2(a + 13*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 /\ a + 13*b >= 0 ] We thus obtain the following problem: 15: T: (1, 14) f3(a, b, c) -> f2(a + 13*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 /\ a + 13*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 13*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 /\ a + 13*b >= 0 ] with all transitions in problem 15, the following new transition is obtained: f3(a, b, c) -> f2(a + 14*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 /\ a + 13*b >= 0 /\ a + 14*b >= 0 ] We thus obtain the following problem: 16: T: (1, 15) f3(a, b, c) -> f2(a + 14*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 /\ a + 13*b >= 0 /\ a + 14*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a + 14*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 /\ a + 13*b >= 0 /\ a + 14*b >= 0 ] with all transitions in problem 16, the following new transition is obtained: f3(a, b, c) -> f2(a + 15*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 /\ a + 13*b >= 0 /\ a + 14*b >= 0 /\ a + 15*b >= 0 ] We thus obtain the following problem: 17: T: (1, 16) f3(a, b, c) -> f2(a + 15*b, b, c) [ a + b >= 0 /\ a + 2*b >= 0 /\ a + 3*b >= 0 /\ a + 4*b >= 0 /\ a + 5*b >= 0 /\ a + 6*b >= 0 /\ a + 7*b >= 0 /\ a + 8*b >= 0 /\ a + 9*b >= 0 /\ a + 10*b >= 0 /\ a + 11*b >= 0 /\ a + 12*b >= 0 /\ a + 13*b >= 0 /\ a + 14*b >= 0 /\ a + 15*b >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b, c) [ a + b >= 0 ] start location: f3 leaf cost: 1 Complexity upper bound ? Time: 2.458 sec (SMT: 2.344 sec)